The Determination of the Parameters of a Vibration Machinef the Internal Compaction of Concrete Mixtures - Maslov, Alexander; Batsaikhan, janar; Puzyr, Ruslan; Salenko, Yulia (International Journal of Engineering and Technology, 2018)
The determination of the rational parameters of a vibration machine for the internal compaction of concrete mixtures. We researched the â€œvibration machine â€“ concrete mediumâ€ system wherein the concrete medium is represented by a system with distributed parameters that takes into account the resilient, viscous, inertial and energy properties of the compacted concrete medium. We researched the propagation of the viscous-resilient-plastic deformation waves in the contracted concrete mixture represented in the form of a half-space. We determined the amplitudes of the oscillations and stresses occurring in the compacted mixture depending on its physical and mechanical characteristics. We determined the oscillation amplitude of the vibration machine, identified its rational parameters. We determined the regularity of the motion of the compacted mixture and the vibration machine depending on the physical and mathematical characteristics of the compacted mixture, the thickness and width of the compacted layer, the angular oscillation frequency and the amplitude of the exciting force. The presented dependences enable the substantiation of the rational parameters of the vibration machine and the modes of vibratory action.Â